Comparison of anaesthetic efficacy of ropivacaine (0.75% & 0.5%) with 2% lignocaine with adrenaline (1:200000) in surgical extraction of bilateral mandibular 3rd molars using IANB:a prospective, randomized, single blind study - Kamil N. Rajpari; Neelam N. Andrade; Trupti Nikalje (Elsevier, 2021)
Aim: To evaluate and compare the anaesthetic efficacy of 0.75% ropivacaine and 0.5% ropivacaine with 2% lignocaine with 1:200000 Adrenaline (LWA) for surgical extraction of bilateral mandibular 3rd molars using Direct inferior alveolar nerve block (IANB). Material and methods: Total of 60 outpatients of both sex,age group of 18-40 included in a prospective, randomized, single blind, split mouth clinical study after satisfying inclusion and exclusion criteria. Group I includes 30 patients and 0.75% ropivacaine as test drug, Group II includes 30 patients and 0.5% ropivacaine as test drug. In both group control drug was LWA.Parameters measured were onset of action, duration of action, systolic blood pressure, diastolic blood pressure, heart rate, visual analogue scale (VAS), faces pain scale (FPS). Result: Onset of action of 0.75%/0.5% ropivacaine (101.84 ​± ​16.92 ​secs/113.03 ​± ​12.77 ​sec) was faster than LWA (Group I-218 ​± ​21.51 ​secs, Group II-196.47 ​± ​26.27 ​secs). Duration of action of 0.75%/0.5% ropivacaine (343.55 ​± ​16.44 ​mins/319.03 ​± ​19.30 ​mins) was longer than 2% Lignocaine with 1:200000 adrenaline (Group I I-173 ​± ​16.86 ​mins, Group II-175.20 ​± ​18.02 ​mins). In Group I - VAS/FPS of 0.75% Ropivacaine (0.97 ​± ​0.54/1.32 ​± ​0.65) was significantly lower as compared to LWA (2.90 ​± ​0.83/3.29 ​± ​0.69). In group II-VAS/FPS of 0.5% ropivacaine (1.40 ​± ​0.72/1.47 ​± ​0.50) was lower as compared to LWA (3.40 ​± ​0.89/3.30 ​± ​0.87). Mean systolic blood pressure, diastolic blood pressure, heart rate was lower for ropivacaine (0.75%, 0.5%) than LWA except mean heart rate higher for 0.75% ropivacaine at 10 ​min after injection. Else mean heart rate lower in other time interval. Conclusion: Ropivacaine (0.75%,0.5%) was more efficacious than 2% lignocaine with adrenaline (1:200000) it terms of all measured parameters in study.